Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Perusahaan Manufaktur Keluarga Di BEI - Alvin, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to obtain empirical evidence about the effect of Good Corporate Governance (GCG) on financial performance with Net Working Capital Turnover as a mediating variable on family manufacturing companies listed on the Stock Exchange in 2016-2018. The sample in this study used a purposive sampling method with a total sample of 93 data. Data processing techniques using bootstrapping with Smart PLS 3.0 software. The results of this study indicate that Good Corporate Governance does not affect the Net Working Capital Turnover. The results of this study indicate that institutional ownership, the board of commissioners, and committees have a positive influence on financial performance. This study also shows that the general meeting of shareholders and Net Working Capital Turnover has no effect on financial performance.